Marriage Age Affects Educational Gender Inequality: International Evidence - Alexander Stimpfle; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2016)
This paper examines the effect of female age at marriage on female education and educational gender inequality. We provide empirical evidence that early female marriage age significantly decreases female education with panel data from 1980 to 2010. Socio-cultural customs serve as an exogenous identification for female age at marriage. We also show that effects of spousal age gaps between men and women significantly affect female education relative to male education. Each additional year between husband and wife reduces the female secondary schooling completion rate by 14 percentage points, the time women spend at university by 6 weeks, and overall affects female education significantly more negatively than male education. We also document that marriage age and conventional measures of gender discrimination do not act as substitutes.
Keywords: J12; J16; I24; O47; 330; Marriage age; spousal age gap; female education; gender inequality